2021
DOI: 10.3390/jof7050396
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Anastomosis Grouping of Rhizoctonia spp. Inducing Black Scurf and Greyish-White Felt-Like Mycelium on Carrot in Sweden

Abstract: Carrots with different Rhizoctonia-like symptoms were found in the main Swedish carrot production areas from 2001–2020. The most commonly observed symptoms were a greyish-white felt-like mycelium and black scurf, the latter often associated with Rhizoctonia solani anastomosis group (AG) 3-PT on potato. An overall increase in disease incidence in all studied fields over time was observed for both symptoms. The majority of Rhizoctonia isolates sampled from carrot in the period 2015–2020 were identified as AG 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Morphological differences among AG5 isolates isolated from carrots in Sweden were also observed by Marcou et al (2021). Singh et al (2018) observed the characteristics of R. solani isolated from seven agroecological zones that were adapted to maize cultivation in 2018.…”
Section: P O S T P R I N Tmentioning
confidence: 84%
“…Morphological differences among AG5 isolates isolated from carrots in Sweden were also observed by Marcou et al (2021). Singh et al (2018) observed the characteristics of R. solani isolated from seven agroecological zones that were adapted to maize cultivation in 2018.…”
Section: P O S T P R I N Tmentioning
confidence: 84%
“…Symptoms and sclerotia formation on carrot and potato plants by AG-3 group was reported for the first time from Sweden. It was reported that this situation might have resulted from the intensely practiced potato-carrot rotation and there might have been a transition of the pathogen from potato to carrot (Marcou et al, 2021).…”
Section: Rhizoctonia Solani As a Pathogenmentioning
confidence: 99%
“…1,2 R. solani belongs to the phylum Basidiomycota, 3 and is divided into 14 anastomosis groups (AGs), namely AG-1 to AG-13 and AG-BI according to the hyphal fusion of isolates with different genotypic and phenotypic characteristics. [4][5][6] R. solani AG-3 was reported to infect crops such as soybean, 7 potato, 8,9 tobacco, 10 carrot, 11 tomato and onion. 12,13 The pathogen generally causes necrotic lesions on leaves, sheaths and stems.…”
Section: Introductionmentioning
confidence: 99%